2019
DOI: 10.1016/j.ijchp.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between children's overweight and quality of life: A comparison of Sizing Me Up, PedsQL and Kid-KINDL

Abstract: Background/Objective: Overweight and obese children are likely to encounter negative impact on psychological well-being and quality of life (QoL). Hence, for overweight and obese children, measuring QoL could go beyond simply assessing objective medical parameters and cover their physical health, psychological well-being, and social interaction. Generic (Kid-KINDL and Pediatric Quality of Life Inventory [PedsQL]) and weight-related (Sizing Me Up) measures are two major types of QoL measurement instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 33 publications
3
44
0
6
Order By: Relevance
“…12 The Kid-KINDL includes six domains, compared to PedsQL's four domains. 18 In their 2019 comparison study, Pakpour et al 18 also found that the SMU tool was signi cantly related to BMI, and the other two generic instruments (PedsQL and Kid-KINDL) did not.…”
Section: Discussionmentioning
confidence: 97%
“…12 The Kid-KINDL includes six domains, compared to PedsQL's four domains. 18 In their 2019 comparison study, Pakpour et al 18 also found that the SMU tool was signi cantly related to BMI, and the other two generic instruments (PedsQL and Kid-KINDL) did not.…”
Section: Discussionmentioning
confidence: 97%
“…In order to quickly assess the risk of addiction related to activities and applications on the internet and smartphone, three ultra-brief psychometric instruments have been developed that have robust psychometric properties. These are the Smartphone Application-Based Addiction Scale (SABAS; Csibi, Demetrovics, & Szabo, 2016), the Bergen Social Media Addiction Scale (BSMAS; Andreassen et al, 2016;Lin et al, 2018), and the nine-item…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More specifically, all three scales have high internal consistency (e.g., α=0.81 for SABAS [Csibi et al, 2016]; 0.97 for BSMAS [Monacis et al, 2017]; 0.90 for IGDS-SF9 [Wu et al, 2017]). However, to the best of the present authors' knowledge, there is only a little information concerning test-retest reliability of the three scales (test-retest reliability=0.83 for SABAS [Lin et al, 2018] and 0.87 for IGDS-SF9 [Wu et al, 2017]). Furthermore, no previous studies have ever examined whether any of them are time invariant across several months.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the adverse effects in social health include such consequences as being bullied (e.g., being isolated or teased) [10]. Numerous studies also demonstrate the negative impacts of being overweight on children's overall health or quality of life (QoL) [10][11][12][13][14][15]. The negative health consequences together with the relatively high prevalence rates of being overweight make the issue of childhood obesity one of the world's major health concerns.…”
Section: Introductionmentioning
confidence: 99%